Graphene Oxide/Copper Nanoderivatives-Modified Chitosan/Hyaluronic Acid Dressings for Facilitating Wound Healing in Infected Full-Thickness Skin Defects - Yang Y (Dove Medical Press, 2020)
Ying Yang,1,2 Zhonggen Dong,3 Min Li,4 Lihong Liu,1,3 Hang Luo,1 Pu Wang,2 Dou Zhang,1 Xinghua Yang,2 Kechao Zhou,1 Shaorong Lei2 1State Key Laboratory of Powder Metallurgy, Research Institute of Powder Metallurgy, Central South University, Changsha 410083, People’s Republic of China; 2Department of Plastic Surgery, Xiangya Hospital, Central South University, Changsha 410008, People’s Republic of China; 3Department of Orthopedic Surgery, Second Xiangya Hospital, Central South University, Changsha 410011, People’s Republic of China; 4Department of Oncology, Changsha Central Hospital, University of South China, Changsha 410004, People’s Republic of ChinaCorrespondence: Shaorong LeiDepartment of Plastic Surgery, Xiangya Hospital, Central South University, 87 Xiangya Road, Changsha 410008, Hunan, People’s Republic of ChinaTel +86 73189753014Fax +86 73184327332Email leishaorong@csu.edu.cnKechao ZhouState Key Laboratory of Powder Metallurgy, Research Institute of Powder Metallurgy, Central South University, 932 South Lushan Road, Changsha 410083, Hunan, People’s Republic of ChinaTel +86 7318836264Fax +86 7318883646Email zhoukechao@csu.edu.cnPurpose: Wound healing, especially of infected wounds, remains a clinical challenge in plastic surgery. This study aimed to manufacture a novel and multifunctional wound dressing by combining graphene oxide/copper nanocomposites (GO/Cu) with chitosan/hyaluronic acid, providing significant opportunities for the therapy of wound repair in wounds with a high risk of bacterial infection.Methods: In this study, GO/Cu-decorated chitosan/hyaluronic acid dressings (C/H/GO/Cu) were prepared using sodium trimetaphosphate (STMP) crosslinking and the vacuum freeze-drying method, and chitosan/hyaluronic acid dressings (C/H) and GO-incorporated chitosan/hyaluronic acid dressings (C/H/GO) served as controls. The surface characterization, in vitro degradation under various pH values, antimicrobial potential, cytocompatibility and in vivo therapeutic efficacy in a bacteria-infected full-thickness skin defect model were systematically evaluated.Results: Our experimental results indicated that the acidic environment facilitated the release of copper (CuNPs and Cu2+) from the dressings, and prepared C/H/GO/Cu dressings exhibited significant in vitro antimicrobial activities against the two tested bacterial strains (ATCC35984 and ATCC25923). All three dressings showed satisfactory cytocompatibility with mouse fibroblasts (NIH/3T3-L1). Moreover, remarkably accelerated wound healing was found in the C/H/GO/Cu group, with controlled inflammatory infiltration and improved angiogenesis in granulation tissues. In addition, no pathological damage was noted in the tissue structures of the tested organs (heart, lung, liver and kidney) in any of the four groups.Conclusion: Collectively, GO/Cu-incorporated chitosan/hyaluronic acid dressings suggested a synergistic antimicrobial efficacy and acceptable biocompatibility both in vitro and in vivo, as well as a significantly accelerated healing process of bacteria-infected wounds. Thus, the multifunctional C/H/GO/Cu composite is expected to be a potential alternative for wound dressings, especially for the management of intractable wounds caused by bacterial infection.Keywords: graphene oxide, copper nanoparticles, wound dressing, bacterial infection, wound healing